Endothelial dysfunction: comparative evaluation of ultrasound dopplerography, laser dopplerflowmetry and direct monitoring of arterial pressure for conducting pharmacological tests in rats - Vladislav O. Soldatov; Tatyana N. Malorodova; Tatiana I. Balamutova; Andrey O. Ksenofontov; Anton P. Dovgan; Zhanna S. Urozhevskaya (Belgorod National Research University, 2018)
Introduction: The importance of the problem of endothelial dysfunction makes it essential to improve approaches to its evaluation. Due to the high diagnostic potential of ultrasound dopplerography, this method is promising in the study of endothelial function. Objective:To study endothelial function when conducting vascular pharmacological tests in the norm and with the blockade of the nitric oxide synthesis by means of the ultrasound method for examining the central blood flow velocity in the femoral artery of the rat in comparison with changes of systemic haemodynamics and microcirculation velocity in the medial vastus muscle using laser Doppler flowmetry. Materials and methods: In the norm and in conditions of deficiency of endogenous nitric oxide, three methods for assessing haemodynamics were used simultaneously: 1) dopplerography using the ultrasoundDoppler system (Minimax-Doppler-K, St Petersburg); 2) laser doppler flowmetry using the TDS144 sensor (Biopac MP-150, USA); 3) recording the arterial pressure in the carotid artery by means of a catheter connected to a TDS-160-A sensor (Biopac MP-150, USA). To study the vasoregulatory function of the endothelium under conditions of multicomponent monitoring of haemodynamics, functional vascular tests were performed using acetylcholine and sodium nitroprusside. Results: Quantification of endothelial dysfunction when conducting pharmacological tests with endothelium-dependent (acetylcholine) and endothelium-independent (sodium nitroprusside) vasodilation is most significant when calculating the coefficient reflecting the ratio of areas of vascular response. Theblood flow velocity parameters recorded by using Doppler ultrasound showed a high correlation level with both arterial pressure and with a linear microcirculation rate. The most comprehensive dopplerographic indices for evaluating the function of the endothelium by conducting pharmacological tests in the norm and in the case of pathology, are the estimated systolic-diastolic difference in blood flow velocities (ΔVs-Vd) in the femoral artery. The study of the endothelial function when conducting vascular pharmacological tests in the norm and with nitric oxide synthesis blockaded, by means of the ultrasound examination of the central blood flow velocity in the femoral artery, is comparable to changing the haemodynamics parameters as well as velocity in microcirculation of the medial vastus muscle using laser Doppler flowmetry. Conclusions: Ultrasonic dopplerography using the Minimax-Doppler-K device reflects the systemic and local vascular response to the administration of vasodilators both in the norm and with the blockade of the nitric oxide synthesis and makes it possible to conduct an informative assessment of the endothelial function.